Synthesis and characterization of alumina-chitosan modified monolithic activated carbon biosorbent from oil palm empty fruit bunches for acid mine drainage remediation - saisa, saisa; ELVITRIANA, ELVITRIANA; SARTIKA, ZULHAINI; ERDIWANSYAH, ERDIWANSYAH (Universitas Syiah Kuala, 2025)
This study reports the synthesis and characterization of a monolithic activated carbon adsorbent modified with alumina and chitosan (Al-Chit/OAC), derived from oil palm empty fruit bunches (OPEFB). The adsorbent was fabricated through pyrolysis, followed by alumina incorporation and chitosan impregnation. FTIR analysis confirmed the presence of functional groups including OH stretching (3640cm), CH stretching (2920cm), CN/CO stretching (10551031cm), and AlO vibrations (693, 522, 495cm), indicating successful surface modification. TGA revealed two major stages of thermal degradation, with a total mass loss of 17.4% and a final residue of 17.55%, reflecting the presence of thermally stable inorganic components. SEM imaging showed a heterogeneous and porous surface with agglomerated particles and interparticle voids, suggesting enhanced surface accessibility. Even though we didn't test how well it absorbs substances, the physical and chemical properties of the composite show it could be very useful for cleaning up acid mine drainage (AMD) in the future. Further studies are recommended to validate its adsorption performance.